Aluminum alloy material suitable for photovoltaics and preparation method thereof

By optimizing the chemical composition and process processing of aluminum alloy materials, the problem of deterioration of aluminum profiles when increasing strength is solved, and the effects of high strength, high toughness and efficient extrusion are achieved, meeting the needs of the solar photovoltaic power generation industry.

CN119899963AActive Publication Date: 2025-04-29ZHEJIANG JINFEI KAIDA WHEEL
View PDF 25 Cites 0 Cited by

Patent Information

Application Number
CN202510398146.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

While increasing the strength, the toughness of existing aluminum profiles decreases, resulting in a decrease in extrusion speed, making it difficult to meet the requirements of the solar photovoltaic power generation industry for production efficiency and cost.

Method used

By optimizing the chemical composition of aluminum alloy materials, adjusting the proportion of elements such as Si, Mg, Ti, Zr, etc., combining the supercooled phase formation and the action of intermetallic compounds, the strength and toughness of aluminum alloys are improved, and the mechanical properties of the material are enhanced through high-temperature fast-cooling quenching treatment and low-temperature long-term aging treatment process.

Benefits of technology

It realizes the high strength and toughness of aluminum profiles, improves the extrusion efficiency, meets the requirements of the solar photovoltaic power generation industry for high-strength aluminum profiles, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899963A_ABST
    Figure CN119899963A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of alloy materials, in particular to an aluminum alloy material suitable for photovoltaics and a preparation method of the aluminum alloy material. The invention provides an aluminum alloy material suitable for photovoltaics, which comprises the following components in percentage by mass: 0.75-0.85% of Si; 0.70% to 0.80% of Mg; ti: 0.05 to 0.20%; zr: 0.05 to 0.18%; 0.01 to 0.03 percent of Mn; 0.10% or less of Fe; cu is less than or equal to 0.03%; less than or equal to 0.05% of Cr; 0.05% or less of Zn; the aluminum alloy material further meets the conditions that Si / Mg is larger than or equal to 1.08 and smaller than or equal to 1.18, and Ti + Zr is larger than or equal to 0.10% and smaller than or equal to 0.30%. The aluminum alloy material suitable for photovoltaics can be used for casting rods, ingots and other products and can be subsequently used for high-pressure casting, extrusion forging and other products, and the strength and toughness of the aluminum alloy material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of alloy material preparation, and in particular to an aluminum alloy material suitable for photovoltaics and a preparation method thereof. Background Art

[0002] The bracket is an important component for supporting and fixing solar photovoltaic power generation devices. Solar photovoltaic power stations are mostly built in areas with good and long sunlight and sparse population (such as deserts, Gobi, grasslands, beaches, etc.). They need to withstand the test of harsh environments such as strong sandstorms, heavy snow or marine moisture. This puts forward higher requirements on the key quality indicators of the supporting bracket, such as strength, weather resistance, corrosion resistance, etc., to ensure its overall strength, operational stability and service life.

[0003] The Chinese patent application with publication number CN113073239A discloses a solar photovoltaic frame bracket aluminum alloy material and a manufacturing method. The aluminum alloy material is composed of the following components in mass percentage: Si 0.57~0.63%, Mg 0.45~0.5%, Mn 0.03~0.07%, Cu 0~0.05%, Cr 0~0.02%, Fe 0~0.1%, Zn 0~0.02%, Ti 0.08~0.12%, and the rest is Al. The tensile strength of the aluminum alloy material is ≥270MPa, the specified plastic extension strength is ≥250MPa, and the elongation is ≥10%.

[0004] The Chinese patent application with publication number CN114908274A discloses an aluminum alloy and profile production process for a solar tracking photovoltaic support bracket. The aluminum alloy material is composed of the following components in mass percentage: Si 0.7~0.9%, Fe 0~0.25%, Cu 0~0.1%, Mn 0.2~0.3%, Mg 0.5~0.7%, Zn 0.1~0.2%, Cr 0~0.01%, Ti 0.05~0.1%, the total content of other impurities is ≤0.15%, and the balance is aluminum. The tensile strength of the aluminum alloy profile is 291MPa, the specified plastic elongation strength is 271MPa, and the elongation after fracture is 10.5%.

[0005] From the production practice and literature retrieval results, the strength of aluminum profiles is still low, which is difficult to meet the future lightweight requirements. In addition, as the strength of aluminum profiles increases, its toughness decreases, and with the decrease in extrusion speed, the production efficiency is reduced, which makes it difficult to meet the development requirements of the solar photovoltaic power generation industry to reduce production costs. Therefore, the development of a new high-strength and tough aluminum alloy material for solar photovoltaic frame brackets has become an urgent problem to be solved in the industry. Summary of the invention

[0006] The purpose of the present invention is to optimize the design of the alloying element composition ratio in response to the above-mentioned problems and deficiencies, so as to solve the problem that the extrusion efficiency and material properties of the solar tracking photovoltaic support bracket cannot be taken into account at the same time; to provide an aluminum alloy material suitable for photovoltaics and a preparation method thereof, to improve the strength and production efficiency of the aluminum profile, to meet the requirements of the solar photovoltaic frame bracket for the aluminum profile, and to reduce the production cost.

[0007] To achieve the above object, the present invention provides the following technical solutions: An aluminum alloy material suitable for photovoltaics includes the following components by mass percentage: Si: 0.75-0.85%; Mg: 0.70-0.80%; Ti: 0.05-0.20%; Zr: 0.05-0.18%; Mn: 0.01-0.03%; Fe≤0.10%; Cu≤0.03%; Cr≤0.05%; Zn≤0.05%; and the balance is aluminum.

[0008] Si and Mg can form Mg2Si strengthening phase to significantly enhance the strength of aluminum alloy. The content of Si and Mg cannot be too low, otherwise the strength of the aluminum profile will be insufficient. The content of Si and Mg cannot be too high, otherwise the strength of the aluminum alloy will be too high, making it difficult to increase the extrusion speed. In addition, in addition to forming Mg2Si strengthening phase with Mg, Si also forms intermetallic compounds with Fe, consuming part of Si. Therefore, in order to obtain a sufficient amount of Mg2Si strengthening phase, the ratio of Si to Mg must also be strictly controlled. In the present invention, the mass percentage of Si and Mg satisfies 1.08≤Si / Mg≤1.18. By changing Si / Mg, the Mg2Si strengthening phase in the alloy can be increased, thereby improving the strength of the alloy.

[0009] The addition of Ti can play a role in grain refinement by increasing composition supercooling. During the solidification process, solute redistribution leads to changes in solute concentration at the front of the solid-liquid interface, causing a change in the theoretical solidification temperature, thereby forming supercooling in the liquid phase in front of the solid-liquid interface. This supercooling caused by solute redistribution in front of the solid-liquid interface is called composition supercooling. Composition supercooling can promote grain refinement; Ti combines with Al to form Al3Ti, which plays a role in grain refinement. Al3Ti phase can serve as the core of heterogeneous nucleation during the solidification process of aluminum alloy, which helps to refine the grains, thereby further improving the strength and toughness of the alloy. In addition, Al3Ti phase can significantly improve the strength and hardness of aluminum alloy. It enhances the mechanical properties of the alloy by dispersing in the aluminum matrix and hindering dislocation movement; the addition of excess Ti can weaken the effect of Zr addition on the poisoning of the refiner.

[0010] The addition of Zr can play a role in grain refinement by increasing the supercooling of the components, which can increase the nucleation rate and reduce the grain growth rate. The increase in supercooling will lead to an accelerated cooling rate, so that the grains are cooled down before they have time to grow. In addition, the increase in supercooling will also lead to an increase in the free energy difference between the liquid and solid phases, making the critical nucleus radius smaller, thereby forming more effective nucleus particles. The addition of Zr can form Al3Zr with Al, which can effectively refine the grains of aluminum alloys and play the role of strengthening phase, thereby improving the mechanical properties of the alloy; at the same time, the addition of Zr can increase the recrystallization temperature of the alloy, making it less likely to recrystallize during conventional heat treatment, thereby maintaining the high strength and hardness of the material; Zr can promote the dispersion and uniformity of the Mg2Si strengthening phase in the Al matrix, thereby improving the comprehensive performance of the alloy.

[0011] Furthermore, the mass percentage of the sum of Ti and Zr satisfies: 0.10%≤Ti+Zr≤0.30%.

[0012] Furthermore, an aluminum alloy material suitable for photovoltaics includes the following components in mass percentage: Si: 0.85%; Mg: 0.75%; Ti: 0.15%; Zr: 0.10%; Mn: 0.02%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn≤0.05%; and the balance is aluminum.

[0013] The present invention provides a method for preparing an aluminum alloy material suitable for photovoltaics:

[0014] (1) According to the raw material ratio, add preheated pure magnesium ingots, Al-Si, Al-Mn, Al-Ti, Al-Zr master alloys or recycled raw materials containing the above alloys into the aluminum liquid at 720℃~750℃, degas by electromagnetic stirring, use argon gas and refining agent to spray and refine the aluminum alloy liquid in the aluminum melting furnace, remove the slag and let it stand; (2) The aluminum alloy liquid is semi-continuously cast at a temperature of 720°C to 750°C and a casting speed of 90 to 110 mm / min to form an aluminum alloy material suitable for photovoltaics.

[0015] Furthermore, the frequency of electromagnetic stirring is 20-40 Hz, the time of electromagnetic stirring is 5-10 min, the amount of refining agent is 0.10-0.20 kg / t, the refining time is more than 8-12 min, and the number of refining times is 2-4 times.

[0016] The present invention also provides a method for preparing aluminum alloy profiles suitable for photovoltaics, which is characterized by: using "online high-temperature rapid cooling quenching treatment" and "low-temperature long-term aging treatment process" to give full play to the superposition effect of a series of strengthening mechanisms. It includes the following steps: The above aluminum alloy material suitable for photovoltaics is heated to above 460-500°C, the extrusion die is heated to 460-470°C, the outlet temperature is 530-550°C, and an air cooling process is used to obtain an aluminum alloy profile suitable for photovoltaics.

[0017] Furthermore, the prepared aluminum alloy profile suitable for photovoltaics is artificially aged at a temperature of 175-195° C. for 4-8 hours.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention combines various strengthening effects of aluminum alloy, such as excess phase strengthening, dispersion strengthening, and fine grain strengthening, by adjusting the chemical composition of Si, Mg, Ti, and Zr.

[0019] (2) Utilizing the high-temperature solid solution effect during the extrusion molding process, rapid cooling is performed through online quenching to form a supersaturated solid solution, and aging hardening treatment is performed to uniformly precipitate the internal strengthening phase to achieve a strengthening effect; (3) The profiles made of the aluminum alloy of the present invention have a tensile strength of ≥330 MPa, a specified plastic elongation strength of ≥315 MPa, and an elongation after fracture of ≥14%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a 50x microstructure photograph of the aluminum profile of Example 2; Figure 2 This is a 50x microstructure photograph of the aluminum profile of Comparative Example 3. DETAILED DESCRIPTION

[0021] Example 1 An aluminum alloy material suitable for photovoltaics, comprising the following components by mass percentage: Si: 0.75%; Mg: 0.70%; Ti: 0.05%; Zr: 0.05%; Mn: 0.01%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0022] The mass percentage of Si and Mg does not satisfy: 1.08≤Si / Mg≤1.18.

[0023] The mass percentage of the sum of Ti and Zr satisfies: 0.10%≤Ti+Zr≤0.30%.

[0024] The specific preparation method is as follows: (1) According to the composition and mass percentage of the aluminum alloy, 47.25 kg of aluminum ingots with a purity of 99.7%, 0.35 kg of magnesium ingots with a purity of 99.8%, 1.88 kg of Al-20Si, 0.25 kg of Al-10Ti, 0.25 kg of Al-10Zr, and 0.03 kg of Al-20Mn were selected as raw materials for batching, and manual inspection and fine-tuning were subsequently carried out to ensure that the composition of the final product met expectations; Among them, Al-20Si means that the mass of Si in the alloy accounts for 20% of the mass of the alloy; Al-10Ti means that the mass of Ti in the alloy accounts for 10% of the mass of the alloy; Al-10Zr means that the mass of Zr in the alloy accounts for 10% of the mass of the alloy; Al-20Mn means that the mass of Mn in the alloy accounts for 20% of the mass of the alloy.

[0025] (2) The raw materials were added into a regenerative gas-fired aluminum melting furnace and heated at 740°C to melt into aluminum alloy liquid. Then, an electromagnetic stirring device was used with a stirring frequency of 30 Hz for 8 min. (3) Use argon gas with a purity of 99.99% and a refining agent of 0.150 kg / t to spray and refine the aluminum alloy liquid in the aluminum melting furnace for 10 minutes, repeat the refining three times, and let it stand for 25 minutes after slagging; (4) semi-continuously casting the aluminum alloy liquid at a temperature of 730° C. and a casting speed of 105 mm / min into an aluminum alloy round rod, i.e., an aluminum alloy material; (5) The aluminum alloy round bar is heated to above 480°C, the extrusion die is heated to 465°C, the outlet temperature is 540°C, and the thin-walled profile is produced using an air cooling process; (6) The obtained extruded profile is artificially aged at a temperature of 195° C. for 4 hours. After cooling, the high-strength aluminum profile for the solar photovoltaic bracket is obtained.

[0026] The properties of the aluminum alloy profile prepared in Example 1 are shown in Table 1.

[0027] Example 2 An aluminum alloy material suitable for photovoltaics, comprising the following components by mass percentage: Si: 0.80%; Mg: 0.75%; Ti: 0.10%; Zr: 0.10%; Mn: 0.01%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0028] The mass percentage of Si and Mg does not satisfy: 1.08≤Si / Mg≤1.18.

[0029] The mass percentage of the sum of Ti and Zr satisfies: 0.10%≤Ti+Zr≤0.30%.

[0030] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 46.60 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.00 kg of Al-20Si, 0.50 kg of Al-10Ti, 0.50 kg of Al-10Zr, and 0.03 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Example 2 are shown in Table 1.

[0031] Example 3 An aluminum alloy material suitable for photovoltaics, comprising the following components by mass percentage: Si: 0.80%; Mg: 0.75%; Ti: 0.15%; Zr: 0.10%; Mn: 0.02%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0032] The mass percentage of Si and Mg does not satisfy: 1.08≤Si / Mg≤1.18.

[0033] The mass percentage of the sum of Ti and Zr satisfies: 0.10%≤Ti+Zr≤0.30%.

[0034] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 46.32 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.00 kg of Al-20Si, 0.75 kg of Al-10Ti, 0.50 kg of Al-10Zr, and 0.05 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Example 3 are shown in Table 1.

[0035] Example 4 An aluminum alloy material suitable for photovoltaics, comprising the following components by mass percentage: Si: 0.85%; Mg: 0.75%; Ti: 0.15%; Zr: 0.10%; Mn: 0.02%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0036] The mass percentage of Si and Mg satisfies: 1.08≤Si / Mg≤1.18.

[0037] The mass percentage of the sum of Ti and Zr satisfies: 0.10%≤Ti+Zr≤0.30%.

[0038] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 46.20 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.13 kg of Al-20Si, 0.75 kg of Al-10Ti, 0.50 kg of Al-10Zr, and 0.05 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Example 4 are shown in Table 1.

[0039] Example 5 An aluminum alloy material suitable for photovoltaics, comprising the following components by mass percentage: Si: 0.80%; Mg: 0.75%; Ti: 0.20%; Zr: 0.15%; Mn: 0.03%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0040] The mass percentage of Si and Mg does not satisfy: 1.08≤Si / Mg≤1.18.

[0041] The mass percentage of the sum of Ti and Zr satisfies: 0.10%≤Ti+Zr≤0.30%.

[0042] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 45.80 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.00 kg of Al-20Si, 1.00 kg of Al-10Ti, 0.75 kg of Al-10Zr, and 0.08 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Example 5 are shown in Table 1.

[0043] Example 6 An aluminum alloy material suitable for photovoltaics, comprising the following components by mass percentage: Si: 0.85%; Mg: 0.75%; Ti: 0.20%; Zr: 0.15%; Mn: 0.03%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0044] The mass percentage of Si and Mg satisfies: 1.08≤Si / Mg≤1.18.

[0045] The mass percentage of the sum of Ti and Zr satisfies: 0.10%≤Ti+Zr≤0.30%.

[0046] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 45.67 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.13 kg of Al-20Si, 1.00 kg of Al-10Ti, 0.75 kg of Al-10Zr, and 0.08 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Example 6 are shown in Table 1.

[0047] Example 7 An aluminum alloy material suitable for photovoltaics, comprising the following components by mass percentage: Si: 0.85%; Mg: 0.80%; Ti: 0.20%; Zr: 0.18%; Mn: 0.02%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0048] The mass percentage of Si and Mg does not satisfy: 1.08≤Si / Mg≤1.18.

[0049] The mass percentage of the sum of Ti and Zr does not satisfy: 0.10%≤Ti+Zr≤0.30%.

[0050] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 45.52 kg of aluminum ingots with a purity of 99.7%, 0.40 kg of magnesium ingots with a purity of 99.8%, 2.13 kg of Al-20Si, 1.00 kg of Al-10Ti, 0.90 kg of Al-10Zr, and 0.05 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Example 7 are shown in Table 1.

[0051] Comparative Example 1 An aluminum alloy material, the following components, calculated by mass percentage, are Si: 0.80%; Mg: 0.75%; Mn: 0.01%; Fe≤0.10%; Cu≤0.03%; Cr≤0.05%; Zn≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements, which are not added separately but are inevitably present.

[0052] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 47.60 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.00 kg of Al-20Si, and 0.03 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Comparative Example 1 are shown in Table 1.

[0053] Comparative Example 2 An aluminum alloy material, comprising the following components by mass percentage: Si: 0.80%; Mg: 0.75%; Ti: 0.10%; Mn: 0.01%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements, which are not added separately but are inevitably present.

[0054] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 47.10 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.00 kg of Al-20Si, 0.50 kg of Al-10Ti, and 0.03 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Comparative Example 2 are shown in Table 1.

[0055] Comparative Example 3 An aluminum alloy material, comprising the following components by mass percentage: Si: 0.80%; Mg: 0.75%; Zr: 0.10%; Mn: 0.01%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements, which are not added separately but are inevitably present.

[0056] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 47.10 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.00 kg of Al-20Si, 0.50 kg of Al-10Zr, and 0.03 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Comparative Example 3 are shown in Table 1.

[0057] Comparative Example 4 An aluminum alloy material, comprising the following components by mass percentage: Si: 0.80%; Mg: 0.75%; Ti: 0.22%; Zr: 0.20%; Mn: 0.01%; Fe ≤0.10%; Cu ≤0.03%; Cr ≤0.05%; Zn ≤0.05%; the balance is aluminum. Fe, Cu, Cr, and Zn are impurity elements that are not added separately but are inevitably present.

[0058] The specific preparation method is basically the same as that in Example 1, except that: (1) According to the composition and mass percentage of the aluminum alloy, 45.50 kg of aluminum ingots with a purity of 99.7%, 0.38 kg of magnesium ingots with a purity of 99.8%, 2.00 kg of Al-20Si, 1.10 kg of Al-10Ti, 1.00 kg of Al-10Zr, and 0.03 kg of Al-20Mn were selected as raw materials for batching; The properties of the aluminum alloy profile prepared in Comparative Example 4 are shown in Table 1.

[0059] Table 1 Alloy properties of Examples 1-7 and Comparative Examples 1-4 Tensile strength Rm / MPa Specified plastic elongation strength Rp0.2 / MPa Elongation after fracture A / % Example 1 331 315 14.5 Example 2 335 317 14 Example 3 342 319 14.7 Example 4 350 328 15.3 Example 5 344 322 14.8 Example 6 345 323 15.2 Example 7 334 318 14 Comparative Example 1 290 270 11 Comparative Example 2 310 290 12 Comparative Example 3 312 295 12.5 Comparative Example 4 325 312 13.5 Table 1 Alloy properties of Examples 1-7 and Comparative Examples 1-4, tensile strength Rm, specified plastic extension strength Rp0.2, and elongation after fracture A are all measured by a tensile machine.

[0060] From the alloy properties of Examples 1-7 and Comparative Examples 1-3 in Table 1, it can be seen that the alloy materials in Examples 1-7 all meet the requirements of tensile strength ≥ 330 MPa, plastic extension strength ≥ 315 MPa, and elongation after fracture ≥ 14%. Compared with Comparative Examples 1-3, Examples 1-7 have higher strength and plasticity, meeting the requirements of solar photovoltaic power generation devices for high-strength aluminum profiles. It can be seen that an aluminum alloy material of the present invention has excellent room temperature mechanical properties in extruded products and is suitable for thin-wall weight reduction of solar photovoltaic profiles.

[0061] From the comparison of the alloy properties of Example 3 and Example 4, and the comparison of the alloy properties of Example 5 and Example 6 in Table 1, it can be seen that the alloy properties of Example 4 are higher than those of Example 3, and the alloy properties of Example 6 are slightly higher than those of Example 5. The difference is that neither Example 3 nor Example 5 satisfies the mass percentage of Si and Mg: 1.08≤Si / Mg≤1.18, while both Example 4 and Example 6 satisfy it. It can be seen that the strength of the alloy can be improved by a suitable mass percentage of Si and Mg.

[0062] from Figure 1-Figure 2 Compared with Example 2 and Comparative Example 3, after adding Ti element in Example 1, the Figure 1 The alloy grain size is reduced, and the strengthening phase in the alloy is fine and dispersed; Figure 2 The grain size of the alloy is relatively large. It can be seen that the increase of Ti element can refine the grains and thus enhance the mechanical properties of the alloy.

[0063] From Examples 1-7 and Comparative Example 4, it can be seen that excessive Ti will affect the elongation and reduce the elongation; excessive zirconium will have a toxic effect and reduce the strength. It can be seen that the components of the present invention, Ti: 0.05~0.20%; Zr: 0.05~0.18%, are the best component mass fraction ranges.

[0064] The above specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention.

Claims

1. An aluminum alloy material suitable for photovoltaics, characterized in that: It includes the following components by mass percentage: Si: 0.75-0.85%; Mg: 0.70~0.80%; Ti: 0.05~0.20%; Zr: 0.05~0.18%; Mn: 0.01~0.03%; Fe≤0.10%; Cu≤0.03%; Cr≤0.05%; Zn≤0.05%; the balance is aluminum.

2. The aluminum alloy material suitable for photovoltaics according to claim 1, characterized in that: The mass percentage of Si and Mg satisfies 1.08≤Si / Mg≤1.

18.

3. The aluminum alloy material suitable for photovoltaics according to claim 1, characterized in that: By mass percentage, 0.05%≤Zr≤0.15%.

4. The aluminum alloy material suitable for photovoltaics according to claim 1, characterized in that: By mass percentage, 0.05%≤Ti≤0.15%.

5. The aluminum alloy material suitable for photovoltaics according to claim 1, characterized in that: By mass percentage, 0.10%≤Ti+Zr≤0.30%.

6. The aluminum alloy material suitable for photovoltaics according to claim 1, characterized in that: It includes the following components in mass percentage: Si: 0.85%; Mg: 0.75%; Ti: 0.15%; Zr: 0.10%; Mn: 0.02%; Fe≤0.10%; Cu≤0.03%; Cr≤0.05%; Zn≤0.05%; and the balance is aluminum.

7. A method for preparing an aluminum alloy material suitable for photovoltaics, characterized in that: The method comprises the following steps: (1) According to the composition of the aluminum alloy material suitable for photovoltaics as described in any one of claims 1 to 6, raw materials are proportioned, and preheated pure magnesium ingots, Al-Si, Al-Mn, Al-Ti, Al-Zr master alloys or recycled raw materials containing the above alloys are added to the aluminum liquid at 720°C to 750°C, and the aluminum alloy liquid in the aluminum melting furnace is sprayed and refined with argon and a refining agent after electromagnetic stirring and degassing, and the scum is removed and then allowed to stand; (2) The aluminum alloy liquid is semi-continuously cast at a temperature of 720°C to 750°C and a casting speed of 90 to 110 mm / min to form an aluminum alloy material suitable for photovoltaics.

8. The method for preparing an aluminum alloy material suitable for photovoltaics according to claim 7, characterized in that: In the step (1), the frequency of electromagnetic stirring is 20-40 Hz, the time of electromagnetic stirring is 5-10 min, the amount of refining agent is 0.10-0.20 kg / t, the refining time is more than 8-12 min, and the refining times are 2-4 times.

9. A method for preparing an aluminum alloy profile suitable for photovoltaics, characterized in that: The method comprises the following steps: heating the aluminum alloy material suitable for photovoltaics as described in any one of claims 1 to 8 to above 460-500° C., heating the extrusion die to 460-470° C., with an outlet temperature of 530-550° C., and using an air cooling process to obtain an aluminum alloy profile suitable for photovoltaics.

10. The method for preparing an aluminum alloy profile suitable for photovoltaics according to claim 9, characterized in that: The prepared aluminum alloy profile suitable for photovoltaics is artificially aged at a temperature of 175-195°C for 4-8 hours.

Citation Information

Patent Citations

  • Aluminum alloy material for solar photovoltaic frame support and manufacturing method

    CN113073239A

  • Aluminum alloy for solar tracking photovoltaic bearing bracket and profile production process of aluminum alloy

    CN114908274A

  • High-performance 6XXX aluminum alloy for outer part of electronic product and machining method thereof

    CN105238962A

  • Solar photovoltaic aluminum alloy and preparation method thereof

    CN105803274A

  • Aluminum alloy and manufacturing method

    CN111118353A